Analisis Yuridis Tata Ruang Pertanahan Dan Tata Guna Pertanahan di Indonesia Berdasarkan Undang Undang Agraria di Indonesia - Butar Butar, Tomy Mangaratua; Idham, Idham; Idham, Idham; Idham, Idham (Universitas Medan Area, 2021)
This study aims to examine juridically the procedures for land management and spatial planning based on the laws governing the form of land management in Indonesia to the applicable rules regarding the procedures for managing land spaces in Indonesia. This analysis uses Primary Sources and Secondary Sources, namely legal materials whose contents have binding legal force originating from books, doctrines, and other materials related to land law. The research method used for research purposes, The general purpose of the research is to find out land use planning and land use in Indonesia, specifically being able to provide information on land spatial planning and land use in general relating to current government regulations, literature sources used for primary and secondary legal materials for discussion and analysis